1. Rewrite one equation in terms of one variable.
2. Substitute the expression for the variable from step 1 into the other equation.
3. Solve the resulting equation for the remaining variable.
4. Substitute the value found in step 3 into one of the original equations and solve for the other variable.
5. Check the solution by substituting the values found in step 4 into the other original equation.
6. Write the final solution as an ordered pair.
7. Convert one equation to the form "variable = expression."
8. Substitute the expression for the variable from step 7 into the other equation.
9. Simplify the resulting equation.
10. Solve the resulting equation for the remaining variable.
Put the steps in order that are used to solve the following systems of equations by substitution. don't give me steps in words just put the numbers in order give me 10 steps
x - 2y = 11 --> x = 2y + 11
-16y = 64
-16y - 77 = -13
x - 2(-4) = 11
x + 8 = 11
y = -4
x = 3
-14y - 77 -2y = -13
-7 (2y + 11) -2y = -13
(3, -4)
1 answer